Jamming and percolation in anisotropic random sequential adsorption of straight rigid rods on a two-dimensional triangular lattice - Perino, Ernesto Jesús (2019)
Percolation of linear k-mers (also known as rods or needles) is studied through Monte Carlo simulationsand finite size scaling, in the case of anisotropic random sequential adsorption on the triangular latticeof LxL and periodic boundary conditions. The efects on the percolation threshold of both the size k ofthe species and the anisotropy degree have been studied. Extensive numerical work enables theconfirmation of a non-monotonic size dependence of the threshold in the isotropic case, which becomesmonotonic in the nematic limit. Finally, a complete analysis of critical exponents and universality hasbeen done, showing that the percolation phase transition involved in the system is not affected, havingthe same universality class of the ordinary random percolation.